(untitled) (Asean Journal of Engineering Education, 2024)
Accreditation of engineering programs requires continuous improvement, and a course improvement plan helps accomplish this aim. Student-centered course design components for a particular course in the architectural engineering program is developed at Missouri University of Science and Technology. Method definition is developed and learning objectives, instruction types, and assessment tools are concluded with learning outcomes. Created course improvement plan meets the accreditation requirements partially. Learning outcomes are studied by the help of Bloom’s Taxonomy. Instruction types include traditional lecture learning environment and problem-based learning environment. Content priorities are also help to conclude targeted learning outcomes. Success of proposed curriculum development is measured by survey and the results are used to create course blueprint and assessment matrix. The curriculum for the mentioned course in the case study results in transitioning from the existing learning environment to the desired learning environment which can be used as a sample for similar courses.